Design and Implementation of an Autofocusing Algorithm for the Goniometric Robotic Apparatus for Compound Eyes - Guzmán-Fonseca, Mariana (Instituto Tecnológico de Costa Rica, 2017)
The goniometer robotic apparatus for compound eye at computational physics laboratory at University of Groningen is requiring an autofocus algorithm that is able to capture on focus images for the analysis of compound eye insect for characterization. In the absence of an adequate algorithm that manages to put the camera in a right place, GRACE automation is di cult to search for respective image. That is why, through the present thesis has been designed and implemented an algorithm of autofocus structured in modules which improve the organization of the process to achieve an adequate analysis of compound eyes. It is proposed an algorithm that executes ve techniques of autofocus capability to determine the sharpness in images in several channels, as well as to use some of that techniques to improve the positioning of the camera and acquire focused images.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2017.
Keywords: Algoritmos; GRACE; Medidas; Visión; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics